The caffeine dilemma: unraveling the intricate relationship between caffeine use disorder, caffeine withdrawal symptoms and mental well-being in adults - Mahmut Bodur; Seda Kaya; Merve Ilhan-Esgin; Funda Pınar Çakiroğlu; Ayşe Özfer Özçelik (Cambridge University Press, 2024)
Abstract Objective: This study aimed to explore the relationship between caffeine use disorder (CUD), caffeine withdrawal symptoms and the prevalence of depression, anxiety and stress (DASS) in adults. Design: The study utilised a cross-sectional design to assess the relationships between CUD, caffeine withdrawal symptoms and DASS. Setting: Participants' CUD was evaluated through the Caffeine Use Disorder Questionnaire (CUDQ), while the Depression Anxiety Stress Scale-21 (DASS-21) measured DASS levels. Caffeine withdrawal symptoms and total caffeine intake were calculated based on self-reported consumption of caffeine-rich products. Participants: The study involved 618 participants with an average age of 27·8 (sd 7·8) years. Results: Participants consumed an average of 461·21 (sd 11·09) mg/d of caffeine, showing a positive correlation between CUD and total caffeine intake. The risk of CUD increased alongside levels of DASS. Individuals with caffeine withdrawal symptoms had higher CUDQ and DASS scores. A multiple linear regression model revealed significant associations between total caffeine intake (P < 0·001) and DASS-21 score (P < 0·001) with CUDQ score. Conclusions: The study concluded that caffeine, while recognised for its potential health benefits, also exhibits properties that may lead to addiction. The development of caffeine use disorder and cessation of caffeine intake can increase DASS levels in adults, indicating the need for awareness and appropriate interventions in public health nutrition.